Mengurai Kekacauan Emosional: Analisis Mendalam Cara Orang Tua Untuk Menghadapi Tantrum Pada Anak Usia Dini - Aprianti, Wahyuni Putri; Vitaloka, Wulansari (UIR PRESS, 2025)
Tantrums are often referred to as peaked emotions felt by children aged 2-6 years as a response to unpleasant situations, which can be manifested through behaviors such as rebelling, screaming, throwing things, rolling, and roaring. This study aims to examine the strategies and methods used by parents when dealing with tantrums in early childhood. This research was conducted qualitatively using a case study approach. Data were collected from three parents of young children in Kerinci Regency through observation, interviews and documentation. The thematic analysis model was used to analyze the data. The results of the study explain that there are several main strategies that can be applied by parents when dealing with tantrums in children by giving time for the child to calm down first, then hugging and inviting the child to talk about feelings and causes of tantrums. As well as consistency and patience of parents is the key to success in dealing with tantrums. Future researchers are advised to expand the research subjects and develop intervention programs that can help parents in dealing with tantrums.